2008
DOI: 10.1289/ehp.10906
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Delayed Methylmercury Toxicity after Perinatal Exposure in Metallothionein-Null and Wild-Type C57BL Mice

Abstract: BackgroundAlthough a long latency period of toxicity after exposure to methylmercury (MeHg) is known to exist in humans, few animal studies have addressed this issue. Substantiation of delayed MeHg toxicity in animals would affect the risk evaluation of MeHg.ObjectivesOur goal in this study was to demonstrate the existence of a latency period in a rodent model in which the toxicity of perinatal MeHg exposure becomes apparent only later in life. Our study included metallothionein (MT) knockout mice because stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…We cannot explain how the emergence of delayed neurobehavioral effects resulted from postnatal exposure to Hg 0 at present. In the present study, as described in previous paper (Yoshida et al, 2008), physiological events with acceleration of the aging process may contribute to the delayed Hg 0 toxicity due to postnatal exposure. However, age-related behavioral changes need to be clarified in further experiments.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…We cannot explain how the emergence of delayed neurobehavioral effects resulted from postnatal exposure to Hg 0 at present. In the present study, as described in previous paper (Yoshida et al, 2008), physiological events with acceleration of the aging process may contribute to the delayed Hg 0 toxicity due to postnatal exposure. However, age-related behavioral changes need to be clarified in further experiments.…”
Section: Discussionsupporting
confidence: 65%
“…On the other hand, the emergence of behavioral effects that accompany the aging process after exposure of offspring to low-level Hg 0 has not been studied in detail. However, results revealed that although the behavioral effects are slight, exposure to Hg 0 during developing periods resulted in the emergence of delayed Hg 0 toxicity in older mice, as well as the emergence of delayed methylmercury toxicity after perinatal exposure (Yoshida et al, 2008). The central nervous system is known to be susceptible to mercury and that exposure to Hg 0 causes more severe damage to offspring than adults.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…C. elegans express nearly 50 GSTs (van Rossum et al , 2001), approximately 10 HSPs of the HSP70 family (Heschl and Baillie, 1989), and 2 MTs (Freedman et al , 1993). Our results indicate that some of the same mechanisms are involved in detoxification in C. elegans as have been identified in other model systems (Sacco et al , 1997; Schlawicke Engstrom et al , 2008; Yoshida et al , 2008). …”
Section: Discussionsupporting
confidence: 83%
“…Due to their high cysteine content, MTs have a strong affinity for MeHg. Additionally, MeHg has been shown to induce MT expression (Rising et al , 1995; Tsui and Wang, 2005) and alterations in behavior of MT-null animals (Yoshida et al , 2008). Although GSH, HSP, and MT have been implicated in resistance to MeHg toxicity, researchers have yet to elucidate their precise roles in detoxification.…”
Section: Introductionmentioning
confidence: 99%